2010
DOI: 10.1039/b919100c
|View full text |Cite
|
Sign up to set email alerts
|

Protonic conductivity of nano-structured yttria-stabilized zirconia: dependence on grain size

Abstract: The conductivity of dense ceramics of nanocrystalline yttria-stabilized zirconia (nano-YSZ), with average grain sizes ranging from 13 nm to 100 nm, was measured in wet and dry air as a function of temperature between 30 C and 500 C. Under wet conditions (p H 2 O ¼ 2.3 Â 10 À2 atm) the measured conductivity at low temperatures (<150 C) was found to increase strongly with decreasing grain size, displaying a highly non-linear dependence on grain size. This is interpreted as evidence of the protonic conductivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 11 publications
10
102
1
Order By: Relevance
“…Thus, we confirm earlier results [12,14,16] that YSZ remains an excellent oxygen-ion conductor, even at high pH 2 O. …”
Section: Diffusion Coefficientssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, we confirm earlier results [12,14,16] that YSZ remains an excellent oxygen-ion conductor, even at high pH 2 O. …”
Section: Diffusion Coefficientssupporting
confidence: 93%
“…The concentration of incorporated protons, however, is small compared with the concentration of oxygen vacancies (the equilibrium is on the left hand side even at high pH 2 O [14,15]), and YSZ remains an excellent oxygen-ion conductor under such conditions [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that this is a result of the crossplane measurements being taken across the ALD YSZ columns, which offers little possibility of measuring the conduction through intergranular regions or across grain boundaries. This explanation is supported by previous studies on nanogranular YSZ, measured in a similar temperature regime [19,20].…”
Section: Electrical Characterization Of Ald Ysz (4:1) Filmsupporting
confidence: 75%
“…Recent studies have revealed enhanced proton transport in nano-granular YSZ [9][10][11][13][14][15][16][17][18]; this is due to the high population of vacancies on the grain surface for compensation of space charge potentials in the vicinity of grain boundary regions [19]. Hence, water or hydroxyl groups preferentially adsorb or chemisorb onto the grain surface, which lead to high concentration of protons in nano-granular YSZ compared to micro-granular materials [13][14][15]17,18]. In this respect, it is reasonable that a substantial amount of protons are incorporated into ALD YSZ films comprised of nanoscale grains [9][10][11].…”
Section: Introductionmentioning
confidence: 99%